(3GdEbJUGO hGdShb (B/s - (3GdQhGTj, aJMj YHO GdYRjRs ((3GdbGgQI(B: s (3eDSSI WjHI ddfTQ h GdJhRjY(B, s, 2007)
(3jVe JYQja Yde GdGbJUGO hCNWGA GdJMdjd, GdbhGfjf GdGbJUGOjI, GbJUGOjGJ GdScGf hJfejI GdehGQO GdHTQjI, GdJNWjW GdGbJUGOj aj GdfXe GdeNJdaI, GTJQGc GdYhGed aj GfJGL GdHjFI GdWHjYjI, GdYQV hGdWdH, JhGRf GdeSJgdc HGSJNOGe acQI efMfjGJ GdShGAs
(3HjHdjhZQGajG(B: (3U(B.207s
Keywords: (3GdGbJUGOs; (3GdShbs; (3Gdbhi GdYGedIs